Pengaruh Entrepreneurial Competence dan Business Network untuk Meningkatkan Competitive Advantange: Studi pada Pelaku UMKM Kue Kering di Kota Sukabumi - Riani Fauzia Rahmayanti; R Deni Muhammad Danial; Nor Norisanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted to determine the influence of the entrepreneurial competence variable and the business network variable on the competitive advantage variable in dry cake MSMEs in the city of Sukabumi. The research method used in this research is a descriptive, associative research method using a quantitative approach. The population in this research are Micro, Small and Medium Enterprises (MSMEs) in the culinary sector of the pastry sector spread across several sub-districts in the city of Sukabumi. The population members in this study were 50 members who were registered with the Sukabumi City Diskoperindag (industry and trade cooperative service) for the 2021/2023 period, using a method, namely nonprobability sampling with a saturated sampling type. Using IBM SPSS Version 22 software, as a data analysis technique tool. The results of this research show that all hypotheses are accepted, and it can be interpreted that there is a positive and significant influence between entrepreneurial competence and business networks increasing, so competitive advantage will also increase.